Gender Difference on Internal Equity: Evidence From the Hospitality Industry in Ghana - Peprah, Patricia; Peprah, Williams Kwasi (Archives of Business Research, 2024)
It is a hypothetical position that employees in the hospitality industry in Ghana experience salary disparities based on the gender of the employee. Pay disparities exist because of unconscious biases in areas such as hiring, promotions, performance reviews, and salary decisions. In ensuring equal pay for equal work to fulfill the International Labor Organization (ILO) convention, this study investigated the internal equity pay of the employees in Ghana's hospitality industry based on equal work. This quantitative association study adopted a self-constructed research instrument to measure internal equity pay and randomly selected 350 respondents in the hospitality industry in Ghana to answer the research questionnaires. The respondents were made up of 160(46%) males and 190(54%) females. In looking for the significant difference of gender as related to internal equity pay of the employees in Ghana with a T'Test analysis, the study revealed that, indeed, there was a significant difference in the salary payment of the employees in Ghana. The males were paid more than the females for equal work. Therefore, the study rejected the null hypothesis that there is no significant difference in internal equity pay based on the gender of the employees in the hospitality industry in Ghana. To ensure equal pay for equal work, the management and shareholders of hospitality firms in Ghana are recommended to seek knowledge of the legal requirement of this principle in the Ghana Labor Law and also become compliant with the ILO convention. Furthermore, a conscious effort must be made to ensure equal pay for equal jobs.